Instructor Assessment of Student Writing - Mihor, Sara Ann; Sexton, Kiah; Suralski, Andrew (My University, 2018)
Writing center and composition scholarship emphasizes the importance of focusing on higher-order concerns in writing. However, there is a lack of recent scholarship that examines how instructors perceive student writing. Early scholars have examined the negative effects of focusing primarily on lower-order concerns, classifying them as problems of “performance, or fluency, not of competence” (Bartholomae, 1980, p. 263). In his seminal article, “The Phenomenology of Error,” composition scholar Joseph Williams (1981) described the difference between higher-order concerns and lower-order concerns as “the difference between reading for typographical errors and reading for content”. He argued that instructors read student work more critically than they do the work of their peers, often actively searching for errors in student writing and, thereby, find more errors overall. Other composition scholars, such as Russell Tabbert (1984), said that attention to grammatical errors can distract from content and does little to promote “true literacy”. Within the last thirty years, however, data-driven research into higher and lower-order concerns is lacking.
Color poster with text.
Keywords: Grading and marking (Students); Writing composition; College students; Posters